Glucose Response of Near-Infrared Alginate-Based Microsphere Sensors Under Dynamic Reversible Conditions - Chaudhary, Ayesha (Mary Ann Liebert, Inc., 2011)
BACKGROUND: Minimally invasive optical glucose biosensors with increased functional longevity form one of the most promising techniques for continuous glucose monitoring, because of their long-term stability, reversibility, repeatability, specificity, and high sensitivity. They are based on the principle of competitive binding and fluorescence resonance energy transfer. Moving to the near-infrared region of the spectrum has the potential to improve signal throughput for implanted sensors, but requires a change in dye chemistry that could alter response sensitivity, range, and toxicity profiles. METHODS: The near-infrared dissolved-core alginate microsphere sensors were fabricated by emulsion followed by surface coating by layer-by-layer self-assembly. The particles were characterized for sensor stability, sensor response, and reversibility in deionized water and simulated interstitial fluid. The sensor response to step changes in bulk glucose concentrations was also evaluated under dynamic conditions using a microflow cell unit. Finally, in vitro cytotoxicity assays were performed with L929 mouse fibroblast cell lines to demonstrate preliminary biocompatibility of the sensors. RESULTS: The glucose sensitivity under controlled and dynamic conditions was observed to be 0.86%/mM glucose with an analytical response range of 0–30 mM glucose, covering both the physiological and pathophysiological range. The sensor demonstrated a repeatable, reversible, and reproducible response, with a maximum response time of 120 s. In vitro cytotoxicity assays revealed nearly 95% viability of cells, thereby suggesting that the alginate microsphere sensor system does not exhibit cytotoxicity. CONCLUSIONS: The incorporation of near-infrared dyes shows promise in improving sensor response because of their high sensitivity and improved tissue penetration of infrared light. The sensitivity for the sensors was approximately 1.5 times greater than that observed for visible dye sensors, and the new dye chemistry did not significantly alter the biocompatibility of the materials. These findings provide additional support for the potential application of alginate microspheres and similar systems such as “smart-tattoo” glucose sensors.